The Influence of Coping Strategies on Students' Mental Health in Facing Academic Stress in Higher Education - Naimatul Ardiah; Intan Aryani Putri Yudha; Zilvi Mia Shafira; Amedaria Volawa; Yuliana Nelisma (Jurnal Profesi Guru Indonesia, 2026)
This study aims to analyze the influence of coping strategies on college students' mental health in dealing with academic stress through a literature review approach. Academic stress remains a major psychological issue among higher education students due to increasing academic demands, including assignments, examinations, and thesis completion. Unlike previous reviews that mainly describe coping strategies in general terms, this study specifically identifies distinct coping clusters and examines how different forms of social support contribute to students' mental health outcomes. The method employed is a literature review by analyzing national and international scientific articles published within a specified period. The findings indicate that adaptive coping strategies, particularly problem-focused coping, planning, and active coping, are consistently associated with lower levels of stress, anxiety, and academic burnout, as well as higher psychological well-being. In contrast, maladaptive coping strategies, such as avoidance, procrastination, and self-blame, are linked to poorer mental health outcomes. Furthermore, the review reveals that social support differentially influences coping effectiveness, with face-to-face support from family, peers, and academic communities generally producing stronger protective effects, while digital support provides complementary benefits in maintaining emotional well-being. These findings suggest that interventions in higher education should promote adaptive coping skills and strengthen both offline and online social support systems to enhance students' mental health.